Essential Microenvironment for Thymopoiesis is Preserved in Human Adult and Aged Thymus - J. Shiraishi; M. Utsuyama; S. Seki; H. Akamatsu; M. Sunamori; M. Kasai; K. Hirokawa (Clinical and Developmental Immunology)
Normal human thymuses at various ages were immunohistologically examined in order to determine whether adult or aged thymus maintained the microenvironment for the T cell development and thymopoiesis was really ongoing. To analyze the thymic microenvironment, two monoclonal antibodies (MoAb) were employed. One is MoAb to IL-1 receptor (IL-1R) recognizing medullary and subcapsular cortical epithelial cells of normal infant human thymus. The other is UH-1 MoAb recognizing thymic epithelial cells within the cortex, which are negative with IL-1R-MoAb. Thymus of subjects over 20 years of age was split into many fragments and dispersed in the fatty tissue. However, the microenvironment of each fragment was composed of both IL-1R positive and UH-1 positive epithelial cells, and the UH-1 positive portion was populated with lymphocytes showing a follicle-like appearance. Lymphocytes in these follicle-like portions were mostly CD4+CD8+ double positive cells and contained many proliferating cells as well as apoptotic cells. Thus these follicle-like portions in adult and aged thymus were considered to be functioning as cortex as in infant thymus. Proliferative activity of thymocytes in the thymic cortex and the follicle-like portions definitely declined with advance of age, while incidence of apoptotic thymocytes increased with aging.